Motor competence of brazilian preschool children assessed by TGMD-2 test: a systematic review - Guilherme dos Santos; Mellina Maria do Lago Manso Silva; Martín Dario Villanueva; Josael Pereira da Silva Júnior; Maria Teresa Cattuzzo; Alessandro Hervaldo Nicolai Ré (Revista da Educação Física)
The Gross Motor Development Test (TGMD-2) is a discriminant and norm-referenced test used to assess the competence level of children aged 3 to 10 years. The aim of the present study was to systematically review the results of Brazilian studies that examined the motor development of preschool children using the TGMD-2 test, considering the different regions of Brazil, as well as to analyze the results related to the factors associated with the performance in the test TGMD-2; we reviewed the LILACS and SCIELO databases using the term "TGMD-2" as the descriptor, searching for original published studies from 2007 to 2018, with full text available, in the Portuguese and English languages, which evaluated motor performance in preschool children using TGMD-2; data extraction included items: first author, local, periodical, objectives, design, sample characteristics, test performance results and related factors; quality of the studies was also evaluated. The ten studies included in the review indicated differences in motor performance in different regions. Signs of better motor performance were found in children of private school and who practice physical activity guided by a physical education professional.